Climate change and agriculture in New York and Pennsylvania: risk perceptions, vulnerability and adaptation among farmers. Issue 3 (14th January 2018) - Lane, David; Chatrchyan, Allison; Tobin, Daniel; Thorn, Kaila; Allred, Shorna; Radhakrishna, Rama
Abstract: Climate change impacts on agriculture have been intensifying in the Northeastern United States. In order to encourage the adoption of climate change adaptation and mitigation practices by farmers, it is critical to understand their perspectives on the risks they face and actions they are taking. However, very few empirical studies have considered how farmers are interpreting and responding to climate impacts, risks and opportunities in the Northeast. This study investigates farmer views and decisions related to climate change using data from six farmer focus groups conducted across New York and Pennsylvania. The study examined how farmers perceived climate impacts on their farms, the practices they are willing to adopt, and how perceived risks and vulnerability affect farmers' decision-making related to adaptation and mitigation strategies. Although farmers articulated concern regarding climate impacts, they also made clear that other business pressures, such as profitability, market conditions, labor availability or government regulations were often more critical issues that affected their decision-making. Decisions about adopting climate change adaptation and mitigation practices vary widely, and personal experience with extreme weather and changing seasons affected decision-making. The findings from this study provide improved understanding of farmers' needs and priorities, which can help guide land-grant researchers, extension and policymakers in their efforts to develop and coordinate a comprehensive strategy to address climate change impacts on agriculture in the Northeast.